Emission of Heavy Metals from Galvanic Production Sludge in Water Objects and Soil - Abuzarovich Nasyrov, Ilnar; Sergeevna Lukina, Kristina; Vitalevich Mavrin, Gennady; Afgatovich Kharlyamov, Damir (International Journal of Psychosocial Rehabilitation, 2019)
Galvanic sludge is a waste hazardous to the environment. The composition of galvanic sludge generated in various industries is much diversified, but galvanic sludge contains heavy metal ions as harmful pollutants. Upon that, the content of heavy metal ions in the aqueous extract reflects the mobility degree of elements in the soil, and in the case of the ammonium acetate extract, it reflects the total content of potentially hazardous elements that can, through the transition to the mobile form, have a negative impact on environmental objects. The content of heavy metal ions in the aqueous extract and the extract of the galvanic sludge-acetate ammonia buffer was determined by atomic emission spectroscopy. A series of elements by mass content in an aqueous extract is Si, Mo, Cu, Zn, Cr, B, Fe, Ni, Co, Sb, and Se. A series of elements by mass content in the acetate-ammonium extract is Zn, Si, Mo, Cu, Cr, Fe, B, Mn, Ni, Sr, Co, Al, Se, Sb, and Ba. Due to the high solubility of most galvanic sludge, pollutant pollutants are relatively easily washed into the water phase and pollute water bodies and the environment. The prior polluting heavy metals in the mobile form are in the order of decreasing values: Mo, Cu, Zn, and Cr, which account for more than 99% of the pollution of the aqueous phase with galvanic production sludge. The neutralization of sludge with regard to heavy metals is possible when converted to insoluble forms or removed from the sludge, especially such elements as Mo, Cu, Zn, Cr, Co, and Ni.